Tecnoestresse no trabalho: um estudo sobre antecedentes e consequentes na administração pública brasileira - Finotti, Mariana Ribeiro (Universidade Federal de São Carlos, 2025)
This research aims to analyze the impacts of antecedents and impacts of technostress on consequential factors at work for civil servants in the Brazilian public administration. The term technostress refers to the stress caused by the excessive use of information and communication technologies (ICT), such as computers, smartphones, and other electronic devices. The constant evolution of technology has changed the way organizations operate, bringing both benefits and challenges. Furthermore, the rapidly developing digital transformation in the public sector involves gains in efficiency and agility, as it will lead to improved relationships between public administrations and their stakeholders, resulting in greater citizen satisfaction and, most importantly, a change in bureaucratic and organizational culture. Given the theoretical gap resulting from the lack of studies on technostress in the Brazilian public sector, this study employed a quantitative research approach, using the quantitative survey method with PLS-SEM modeling. The investigation addresses antecedent factors that favor the emergence of technostress and consequential factors involving negative effects arising from technological interaction. A structured questionnaire was used as a data collection instrument, divided into 6 closed questions, on a 5-point Likert scale, sent to public servants from different spheres, electronically. The findings highlight an understanding of organizational factors as triggers of technostress, a predominance of studies on the implications for women, and the negative impacts of technostress on mental health. This study also highlights strategies that promote healthy technology use and ensure a more balanced and productive work environment in public administration. This research contributes to the theoretical discussion of technostress in the workplace, considering both the needs of individuals and organizations to build a balanced relationship. As practical implications for mitigating technostress in public administration, the study suggests guidelines for implementing support and well-being policies, improving the usability of technology in the workplace, and promoting a healthy work-life balance. Furthermore, the survey largely included responses from federal employees, which may limit the generalizability of the results to the entire national public administration, which is characterized by a wide variety of organizational structures. The study's originality also stands out, as it innovatively addresses the individual and organizational factors that can contribute to technostress, as well as their individual and organizational impacts and correlations.
Techno-stress at work: a study on antecedents and consequences in Brazilian public administration
Keywords: Tecnoestresse; Serviço público; Administração pública; Technostress; Public service; Public administration; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; 3. Saúde e Bem-Estar; 8. Trabalho Decente e Crescimento Econômico